SUMOylation Is Essential for Dengue Virus Replication and Transmission in the Mosquito Aedes aegypti - Weng, Shih-Che; Shiao, Shin-Hong (Frontiers in Microbiology, 2022)
Small ubiquitin-like modifier (SUMO) is a reversible post-translational protein modifier. Protein SUMOylation regulates a wide variety of cellular processes and is important for controlling virus replication. Earlier studies suggest that dengue virus envelope protein interacts with Ubc9, the sole E2-conjugating enzyme required for protein SUMOylation in mammalian cells. However, little is known about the effect of protein SUMOylation on dengue virus replication in the major dengue vector, Aedes aegypti. Thus, in this study, we investigated the impact of protein SUMOylation on dengue virus replication in A. aegypti. The transcription of A. aegypti Ubc9 was significantly increased in the midgut after a normal blood meal. Silencing AaUbc9 resulted in significant inhibition of dengue virus NS1 protein production, viral genome transcription, and reduced viral titer in the mosquito saliva. In addition, we showed that dengue virus E proteins and prM proteins were SUMOylated post-infection. The amino acid residues K51 and K241 of dengue virus E protein were essential for protein SUMOylation. Taken together, our results reveal that protein SUMOylation contributes to dengue virus replication and transmission in the mosquito A. aegypti. This study introduces the possibility that protein SUMOylation is beneficial for virus replication and facilitates virus transmission from the mosquito.